1986
DOI: 10.7164/antibiotics.39.762
|View full text |Cite
|
Sign up to set email alerts
|

A new antitumor complex, WF-1360, WF-1360A, B, C, D, E and F.

Abstract: A complex of the new antitumor antibiotics (WF-1360, WF-1360A, B, C, D, E and F) was produced by Rhizopus sp. No. F-1360. Structural studies of these compounds suggested that they were novel 16-membered-ring lactones having an oxazole ring in their structures. WF-1360 was found to be identical with rhizoxin (1) and WF-1360B, C, E and F were determined to be homologues of 1 with structures 2, 3, 4 and 5, respectively. These compounds were cytotoxic when tested on P388 leukemia cells in vitro. WF-1360 was highly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 1 publication
5
43
0
Order By: Relevance
“…Comparison of the metabolite profiles of Pf-5 and an rzxB mutant, derived by allelic-exchange mutagenesis, indicated that the orphan gene cluster was involved in the biosynthesis of at least two compounds with [MϩH] ϩ peaks at 580.7 and 610.3 m/z, respectively (see the supplemental material). From the detected molecular masses and UV spectra, the compounds could be readily dereplicated by a database search as the rhizoxin analogs WF-1360 C and WF-1360 F (25).…”
Section: Resultsmentioning
confidence: 99%
“…Comparison of the metabolite profiles of Pf-5 and an rzxB mutant, derived by allelic-exchange mutagenesis, indicated that the orphan gene cluster was involved in the biosynthesis of at least two compounds with [MϩH] ϩ peaks at 580.7 and 610.3 m/z, respectively (see the supplemental material). From the detected molecular masses and UV spectra, the compounds could be readily dereplicated by a database search as the rhizoxin analogs WF-1360 C and WF-1360 F (25).…”
Section: Resultsmentioning
confidence: 99%
“…We demonstrated that these metabolites are produced by Pseudomonas strains associated with S. latissima. DAPG, MAPG, PLT and rhizoxins are thus proposed to be chemical mediators of antibacterial, antifungal, cytotoxic and antiprotozoal effects for possible protection of the alga, as shown for terrestrial pseudomonad-host plant associations (Iwasaki et al 1984, Kiyoto et al 1986, de Souza et al 2003, Isnansetyo et al 2003, Jousset et al 2006. Both DAPG and PLT produced by the Pseudomonas strains in the present study are able to suppress the algal pathogens Algicola bacterio lytica and Pseudoalteromonas elyakovii.…”
Section: Bioactivity Of Metabolites Produced Bymentioning
confidence: 64%
“…Compound 1 is identical to WF-1360C (20,21), a previously reported analog of the antimitotic agent rhizoxin (Fig. 3).…”
Section: Identification Of New Rhizoxin Analogs Marine Bacterial Isomentioning
confidence: 99%